PENERAPAN STRATEGI PEMBELAJARAN PREDICT-OBSERVE-EXPLAIN (POE) UNTUK MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN IPA SD KELAS IV SDN 006 SENCANO JAYA - Yusrizal Yusrizal (Jurnal Pendidikan, 2020)
This research is motivated by the low student learning outcomes in the historical subjects of class IV IPA at SDN 006 Sencano Jaya. Based on these problems, the formulation of the problem in this study is whether the application of the predict-observe-explain (POE) learning model can improve the learning outcomes of class IV students of SDN 006 Sencano Jaya. The purpose of this study is to find out the activities of teachers and students in the implementation of the learning process by using the predict-observe-explain (POE) model and to determine the effect of this learning model on learning outcomes of students of class IV SDN 006 Sencano Jaya on sains subjects. This research was conducted in two cycles, in the first cycle the learning outcomes of students reached 85.18% classical completeness and increased in the second cycle reached 100%. Based on the results of these studies it can be concluded that the application of the predict-observe-explain (POE) learning model can improve student learning outcomes in the sains lesson of the IV class at SDN 006 Sencano Jaya.